Research on the Technology of Rapid Outburst Elimination Strip by High-Pressure Nitrogen Injection Displacement in Bottom Extraction Roadway for Promoting Flow and Enhancing Permeability - Sun, Rui (Scientific Journal of Technology, 2025)
To address the challenges of difficult gas extraction and outburst elimination in "three-soft" low-permeability outburst coal seams, a rapid strip outburst-elimination technology is proposed, which combines high-pressure nitrogen injection displacement in the bottom drainage roadway for promoting flow and enhancing permeability. This technology was experimentally studied in the upper bottom drainage roadway of 14205 working face in a coal mine. The experimental results show that after nitrogen injection displacement, the total gas flow rate from boreholes increases by an average of over three times compared to conventional conditions, with a peak increase of over six times. The gas content in the coal seam within the displacement area decreases from an average of 6.80 m³/t and 7.56 m³/t to 5.58 m³/t and 4.98 m³/t, respectively, while the gas content outside the displacement area is 7.76 m³/t and 7.5 m³/t. There is a significant difference in gas content between the inside and outside of the displacement area, indicating that nitrogen injection displacement can enhance gas extraction and achieve rapid outburst elimination.